A comprehensive analysis to assess the impact of nano MoS2 on the wear characteristic of Al-TiB2-Gr composite. (1st January 2022) - Chenrayan, Venkatesh; Vaishnav, V.; Shahapurkar, Kiran; Tirth, Vineet; Alarifi, Ibrahim M.; Manivannan, Chandru; Soudagar, Manzoore Elahi M
Abstract: The present study evaluates the influence of nano MoS2 particles on the wear properties of newly developed TiB2 and Graphite reinforced Aluminium composite. Micro particles of MoS2 are downsized into nano levels using a planetary ball mill. Three different compositions of specimens are fabricated through stir casting, with a constant 10% of weight of TiB2, graphite, and nano MoS2 is kept at varying amounts of 10, 15, and 20%. The dry sliding wear tests are executed by following Taguchi's design of experiment. The wear rate and coefficient of friction are considered as responses, whereas the normal load, sliding distance and the composition of MoS2 are considered as the chief parameters with three levels. The hybridized Taguchi-Grey Relational -Principal Component Analysis mathematical model is implemented to study the effect of wear parameters and inclusion of MoS2 on the wear behavior. Mathematical and experimental results explore the increasing nano MoS2 content reduces the wear rate and coefficient of friction of composites. Analysis of variance results also acknowledge that nano MoS2 content in the composite is a remarkable parameter to impact the tribological property. The hybrid statistical model results explore that the optimum parameter to yield better tribological property are 30 N normal load, 2 km sliding distance and 20% of MoS2 . Worn surfaces are analyzed using scanning electron microscopy to picturize the wear mechanism concerning the varying content of reinforcement.